2015
DOI: 10.1364/ao.54.005903
|View full text |Cite
|
Sign up to set email alerts
|

Pixel-level fringing-effect model to describe the phase profile and diffraction efficiency of a liquid crystal on silicon device

Abstract: We propose a fringing-effect model based on the experimentally measured phase response across the phase transition region of a liquid crystal on silicon (LCOS) device. The measured phase profile in the phase transition region is characterized by a scaled error function of the flyback width. The flyback width can be determined by a cubic function of the phase depth between neighboring pixels. This dependence of the flyback width on the phase depth is explained by a linear rotation model of the liquid crystal di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…The reason for this limitation is that downsizing the pixels further while keeping the required thickness of LC layer introduces a cross-talk between the pixels, owing to the broadened phase profile and high level of detrimental fringing fields. [6][7][8][9][10] This, in turn, limits the field of view (FOV) of the SLM, which is defined as the angular coverage of the first diffractive order, inversely proportional to the pixel size, and represents one of the most important figure of merits (FOMs) for phase-only SLMs. This problem is more severe for transmissive SLMs, which have a smaller filling factor due to the space occupied by transistors and an LC thickness that is twice larger than that of reflective SLMs to obtain the same phase accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for this limitation is that downsizing the pixels further while keeping the required thickness of LC layer introduces a cross-talk between the pixels, owing to the broadened phase profile and high level of detrimental fringing fields. [6][7][8][9][10] This, in turn, limits the field of view (FOV) of the SLM, which is defined as the angular coverage of the first diffractive order, inversely proportional to the pixel size, and represents one of the most important figure of merits (FOMs) for phase-only SLMs. This problem is more severe for transmissive SLMs, which have a smaller filling factor due to the space occupied by transistors and an LC thickness that is twice larger than that of reflective SLMs to obtain the same phase accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…This equation is widely used for fast calculation of the expected diffraction efficiency. In another model built by Lu et al [57], the near field phase profile of the grating is observed under a microscope. The profile is then fitted using the error function, and the diffraction efficiency is calculated by the angular spectrum method.…”
Section: Fringing Field Effectmentioning
confidence: 99%
“…Besides the effects produced by the limited electronics bandwidth already described, interpixel effects in the LC layer may also cause a reduction in the spatial frequency bandwidth. These interpixel effects are the fringing-field (i.e., appearance of tangential components in the applied electric field) and vicinity LC adherence effects that appear as a result of the competition between the tangential components of the applied field and the intermolecular forces within the liquid crystals (i.e., avoiding abrupt changes in the orientation) [16][17][18][19][20][21][22]. These interpixel effects are becoming more and more important in modern LCoS devices as the pixel size is becoming increasingly small, even smaller than 4 µm [22], thus decreasing the ratio between the pixel size and the LC layer thickness (i.e., the cell gap).…”
Section: Introductionmentioning
confidence: 99%